Technical Performance of Agriculture Farming Decision Making Entities in Telangana State: A New Integrated Evaluation Using Data Envelopment Analysis (DEA) Approach - Donthula, Pavan Kumar; Nellutla, Raju; Haragopal, V. V. (Communications in Mathematics and Applications, 2023)
The present research paper, we evaluate technical performance of agriculture farming decision making entities Optimality Analytics by CCR and BCC techniques through Data Envelopment Analysis approach for the Telangana state and see that the optimal empirical performances of farming entities with respective to all the districts of the state of Telangana. The district wise agriculture farming decision making entities performances is evaluated by considering the Technical/Pure Technical Efficiency of one district over rest of the districts under various permutations by computing the Efficiency scores, Scale Efficiency (SE), CRS, VRS, References and Peers of the DMUs, and also assign a rank of decision-making units based on the reference sets. Integrated analytical techniques were used to improve the inputs and outputs values of the inefficient DMUs. A new integrated CCR and BCC theoretical models are used to evaluate the performance of the districts for the data are presented in this research paper.